The Empathy Of Consummate Love In Devon Daniels’ Meet You In The Middle - Calista, Salsabila Nova; Smarandreetha, Falsyawal Galang; Ibrahim, Laila Nabilahtuzzahro; Pasopati, Rommel Utungga (Gudang Jurnal Multidisiplin Ilmu, 2024)
This article examines how the novel Meet You in the Middle by Devon Daniels portrays the reason for consummate love that causes a long term relationship, which consists of component love of intimacy, passion, and commitment in Triangular Theory of Love by Sternberg. Then, the reason is rooted in interpretation of empathy. Empathy is a physiological reaction that has three components, they are emotional, cognitive, and motivational. It helps people to understand, feel, and care about others, even if it is sometimes hard. The novel tells the story of Kate Adam and Ben Mackenzie, who are liberal and conservative Senate staffers, respectively, and who fall in love despite their ideological differences and professional rivalry. The article analyzes how the novel depicts the challenges and benefits of empathizing with a romantic partner who has opposing political views, and how empathy contributes to the development and maintenance of consummate love. Then, it concludes that the novel offers a hopeful and realistic message that consummate love can bridge the political divide, as long as the partners are willing to empathize with each other and respect their differences.